From the wireless to the web : the evolution of telecommunications, 1901-2001 - Jensen, Peter R. (University of New South Wales Press, 2000)
"From the Wireless to the Web: The Evolution of Telecommunications 1901 to 2001 is a story of endeavour, from the discovery and development of early radio to the present forms of communication. It describes how there has been a series of technological developments and events that has led inexorably to the achievement of enhanced person-to-person communications, the Internet and the World Wide Web. The book marks the centenary of the first trans-Atlantic radio signal, sent from Poldhu in the United Kingdom to Marconi in St John's, Newfoundland."--Jacket